Application of Restorative Justice Against Oil Palm Theft: Analysis of Islamic Criminal Law Case Study Medan Labuhan District - Muhairina, Nurul; Zulkarnain (Alauddin Law Development Journal (ALDEV), 2024)
Palm oil theft is a common crime in Indonesia, regulated by positive law. However, in the case of theft crimes in Medan Labuhan District, the use of restorative justice and Islamic criminal law is used to resolve these cases. This study aims to analyze the role of restorative justice in handling oil palm theft cases in Medan Labuhan sub-district from the perspective of Islamic criminal law. Restorative justice focuses on restoring relationships between victims and the community through dialogue and mutual attestation, compared to a retributive approach that focuses on providing punishment. This qualitative research, using empirical juridical approaches and field research techniques, concludes that restorative justice in the Islamic criminal law system can be an effective alternative in handling theft cases, especially in the community of Medan Labuhan District. This approach aligns with the principles of shura (deliberation), which prioritize peaceful settlement and the restoration of social relations.